Des tables pascales aux tables astronomiques et retour - Max Lejbowicz (Methodos, 2006)
The article studies the birth and development of the Christian ecclesiastical calendar, i.e. the computus, from the first witnesses to the yearly celebration of the resurrection of Jesus to the translations of arabic astronomical tables in the 12th century. It focuses on the procedures which resulted in determinig the dates of Easter and their being put into tabular form. These analyses were undertaken from two perspectives. One was scientific, relying on the astronomical data preserved by Ptolemy and on the contribution of the Greek mathematical tradition to calculation by approximation. The solar-lunar cycles were presented through continuous fractions and the weekly-solar cycles through the least common multiple. The second perspective was social : the unification of the computus shared in that of Christendom, understood as a politico-religious configuration. This leads to two conclusions. Whatever the importance medieval civilization assigned to the computus, it remains that (1) Easter carries a meaning which is not reducible to the chronometric techniques that fit this feast in the unfolding of the year ; (2) these techniques profoundly shaped the intellectual curiosity of Latin Christendom, and prepared them to welcome with fervor the zīj and positional numeration.